An Ecosystems Perspective on Virus Evolution and Emergence. Issue 3 (March 2020) - French, Rebecca K.; Holmes, Edward C.
Abstract : Understanding the emergence of pathogenic viruses has dominated studies of virus evolution. However, new metagenomic studies imply that relatively few of an immense number of viruses may lead to overt disease. This suggests a change in emphasis, from viruses as habitual pathogens to integral components of ecosystems. Here we show how viruses alter interactions between host individuals, populations, and ecosystems, impacting ecosystem health, resilience, and function, and how host ecology in turn impacts viral abundance and diversity. Moving to an ecosystems perspective will put virus evolution and disease emergence in its true context, and enhance our understanding of ecological processes. Highlights: The high abundance and diversity of viruses in nature, often in the apparent absence of disease, suggests that they are naturally embedded into global ecosystems at all ecological scales. Studies of virus ecology and evolution need to refocus to understand the role played by viruses in global ecosystems rather than only on pathogens that emerge following host jumping. Viruses alter interactions between host individuals, populations, and ecosystems, impacting ecosystem health, resilience, and function. Host ecology in turn impacts viral abundance and diversity. Viruses account for extensive biodiversity and have abundant links within ecosystems. An ecosystem with higher diversity has higher functional redundancy and is more resilient to change. The natural virome may therefore be beneficial to ecosystem function.